1991
DOI: 10.1128/aac.35.7.1298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intravitreal dexamethasone on concentration of intravitreal vancomycin in experimental methicillin-resistant Staphylococcus epidermidis endophthalmitis

Abstract: Intravitreal corticosteroids in the treatment of bacterial endophthalmitis remain controversial. We utilized an experimental rabbit model of methicillin-resistant Staphylococcus epidermidis endophthalmitis (i) to calculate the intravitreal vancomycin concentration in rabbit eyes receiving intravitreal vancomycin alone or in combination with intravitreal dexamethasone and (ii) to determine whether an intravitreal steroid has any effect on intravitreal vancomycin levels. All right eyes were infected and all left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 13 publications
(17 reference statements)
1
18
1
Order By: Relevance
“…Also in ophthalmology, corticosteroids have a beneficial effect on the outcome of endophthalmitis in most animal studies ( [5], [7]). However, two studies ( [8], [10]) reported that dexamethasone may decrease the vancomycin concentrations, a possible concern for their combined use.…”
Section: Introductionmentioning
confidence: 97%
“…Also in ophthalmology, corticosteroids have a beneficial effect on the outcome of endophthalmitis in most animal studies ( [5], [7]). However, two studies ( [8], [10]) reported that dexamethasone may decrease the vancomycin concentrations, a possible concern for their combined use.…”
Section: Introductionmentioning
confidence: 97%
“…However, animal experimental models with Streptococcus pneumoniae and Staphylococcus epidermidis had yielded conflicting results. 19,20 As our in vitro study suggests that loss of vancomycin was minimal, either alone or in the presence of other medications or media, other in vivo variations, such as organism characteristics, host inflammatory response and breakdown of blood-ocular barrier, may account for the opposite results obtained by previous in vivo studies. Smith et al 19 had suggested that the elimination of vancomycin through the canal of Schlemm may be facilitated by the presence of steroids, resulting in lower intraocular levels.…”
Section: Discussionmentioning
confidence: 74%
“…They were also able to demonstrate that early treatment with vancomycin not only eradicated the infection (confirmed microbiologically) but also preserved the retinal architecture (shown histopathologically). In another study, it was reported that in experimental MRSE endophthalmitis when intravitreal dexamethasone was included in the treatment, less intravitreal vancomycin concentration was needed 35 because of this, therapy with a single dose of intravitreal vancomycin together with dexamethasone may be sufficient to treat endophthalmitis with a low-virulence organism such as MRSE.…”
Section: Discussionmentioning
confidence: 95%